Hansen and Public Policy - Tobin, James (Quarterly Journal of Economics, 1976)
Journal Article Hansen and Public Policy Get access James Tobin James Tobin Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 90, Issue 1, February 1976, Pages 32–37, https://doi.org/10.2307/1886084 Published: 01 February 1976